Dynamics of territorial and political conflicts in the world - Slyvka, Roman (Human Geography Journal, 2017)
Application of quantitative approach allows for gaining new results on trends of the dynamics of territorial and political conflicts (TPC). The objective of the article is to determine the dynamics in the number of territorial and political conflicts in individual macro-regions and in the whole world. The task of the article is to give grounds for viability of allocating groups of conflicts characterized by territorial manifestation from HIIK database “Conflict Barometer”; to determine the dynamics of a series of indicators typical of territorial and political conflicts in 2004-2014.Analysis of TPC development in the world using the data presented in the reports of HIIK “Conflict Barometer” (2004, 2006, 2008, 2010, 2012, 2014) was made. Out of all political conflicts characterized by such conflict issues as: 1. Territory; 2. Autonomy; 3. Secession; 4. Subnational Predominance; 5. Resources, TPC sampling was performed. Attention was also paid to TPC, which were characterized by a combination of several conflict issues.It has been established that over the decade under study, the number of conflicts that belong to TPC group has significantly increased from 114 to 253, i.e. in 2.2 times. This increase occurred in a wave-like manner. Over the period under study, the average intensity of TPC in the world has increased. In absolute terms, the largest increase in the number of conflicts took place in Asia and Africa, and the largest relative increase was inAmerica(3.5 times) andOceania(7 times). TPC duration has also grown. The largest number of TPC concerned the authority in the region and autonomy.